Development of Non-Olympic sports in Kharkov region during the existence of the Ukrainian SSR - Nataliia Saltan; Oleksandr Saltan (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the attempt to investigate the history of formation of Non-Olympic sports in our region is made on the basis of the analysis of number of archival documents and materials of periodicals. Material & Methods: the analysis and generalization of the sourced base on the matter. Results: features of the development of the sports branch during the entire period of the existence of the Ukrainian SSR are analyzed. Conclusions: it is established that the development of Non-Olympic sports of the Soviet period began in the 20th of the XX century. Chess and checkers, military-sports kinds (in the conditions of militarization of the country in the 30th of the XX century) and different types of single combats became the most mass among Non-Olympic sports in the region. The level of training of sportsmen of Kharkov was such high that they made the basis of national teams of the Ukrainian SSR, and also were the part of national teams of the Soviet Union.